OUTWARD FOREIGN DIRECT INVESTMENT: EMERGING ECONOMIES’ HOME COUNTRY DETERMINANTS - Kapil, Sheeba; Dhingra, Puneet Kaur (Indian Journal of Finance and Banking, 2021)
The Tendency of firms from emerging economies to invest abroad has increased significantly during the last two decades. Despite this trend, comprehensive literature survey research on macroeconomic determinants and antecedents of outward FDI from emerging economies is still underrepresented. The purpose of this paper is to give a comprehensive understanding of home country level factors’ impact on outward FDI from developing countries through a systematic review of past researches on OFDI’s macroeconomic determinants of home economy. The findings reveal that the most important determinants are, home country market size and openness of home country towards internationalization. However, some researches posted contrasting results for the impact of home country’s interest rates, human capital and technological capability on OFDI from emerging economies. This study also points out that emerging economies suffer from shortage of skilled personnel, thus making human capital an essential push factor for OFDI. JEL Classification Codes: F21, F23, P45.